Clinical Characteristics and Outcomes of Patients with Lung Cancer and Venous Thromboembolism - Ruiz-Artacho, Pedro; Trujillo-Santos, Javier; López-Jiménez, Luciano; Font, Carme; Díaz-Pedroche, María del Carmen; Sánchez Muñoz-Torrero, Juan Francisco; Peris, Maria Luisa; Skride, Andris; Maestre, Ana; Monreal, Manuel; the RIETE Investigators (TH Open, 2018)
Background The natural history of patients with lung cancer and venous thromboembolism (VTE) has not been consistently evaluated.Methods We used the RIETE (Registro Informatizado Enfermedad TromboEmbólica) database to assess the clinical characteristics, time course, and outcomes during anticoagulation of lung cancer patients with acute, symptomatic VTE.Results As of May 2017, a total of 1,725 patients were recruited: 1,208 (70%) presented with pulmonary embolism (PE) and 517 with deep vein thrombosis (DVT). Overall, 865 patients (50%) were diagnosed with cancer <3 months before, 1,270 (74%) had metastases, and 1,250 (72%) had no additional risk factors for VTE. During anticoagulation (median, 93 days), 166 patients had symptomatic VTE recurrences (recurrent DVT: 86, PE: 80), 63 had major bleeding (intracranial 11), and 870 died. The recurrence rate was twofold higher than the major bleeding rate during the first month, and over threefold higher beyond the first month. Fifty-seven patients died of PE and 15 died of bleeding. Most fatal PEs (84%) and most fatal bleeds (67%) occurred within the first month of therapy. Nine patients with fatal PE (16%) died within the first 24 hours. Of 72 patients dying of PE or bleeding, 15 (21%) had no metastases and 29 (40%) had the VTE shortly after surgery or immobility.Conclusion Active surveillance on early signs and/or symptoms of VTE in patients with recently diagnosed lung cancer and prescription of prophylaxis in those undergoing surgery or during periods of immobilization might likely help prevent VTE better, detect it earlier, and treat it more efficiently.
Keywords: venous thrombosis; pulmonary embolism; recurrences; bleeding; anticoagulant therapy; lung cancer